Perzinaan Menurut Pandangan AL-Qur'an (Studi Interpretatif Tematik Ayat-ayat Zina) - Nasiri; Achmad; Afifah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
Adultery is sexual intercourse between a man and a woman without a legal marriage bond. The Qur'an discusses adultery in three surahs, namely The first verse (QS. Al-Isra' verse 32) contains a prohibition on approaching adultery. The second (QS. An-Nur verses 2-3) contains the punishment for adulterers and the prohibition on marrying them, and the third verse (QS. Al-Furqan verse 68) contains the reward for adulterers in the future with Allah. In Islam, the word adultery includes adultery muhshan and ghairu muhshan. The limits of adulterers that must be present are 12 (twelve), namely 1). Mukallaf. 2). Clearly male, 3). Inserting the entire hasyafah (tip of the penis). 4). 5). His genitals are still attached to the person. 6). Inserting his genitals into a woman who is clearly 7). The law prohibiting inserting genitals is in essence 8). The law of prohibition arises from reality 9). There must be no doubt that the genitals cause abortion 10). The genitals must be desired (desired) by nature 11). The perpetrator of adultery must obey Islamic law 12). The perpetrator must understand the prohibition of adultery.